Influence of brominated-TPA-stilbazole based ancillary ligand on the photocurrent and photovoltage in dye-sensitized solar cells. (March 2018) - Ashraf, Saba; Su, Rui; Akhtar, Javeed; Siddiqi, Humaira M.; El-Shafei, Ahmed
Abstract: Two novel heteroleptic brominated-TPA-stilbazole based Ru (II)-sensitizers denoted as SD-11 and SD-11 mono were designed, synthesized and characterized for dye-sensitized solar cells (DSCs) in comparison to benchmarked dye N719. The molecular structures of SD-11 and SD-11 mono were confirmed using FTIR, 1 H-NMR and mass spectrometry. The aim was to systematically study the effect of mono (SD-11 mono) versus bis-brominated-TPA moiety (SD-11) on molar absorptivity, ground and excited state oxidation potentials, light harvesting efficiency (LHE), incident-photon-to-current conversion efficiency (IPCE), short-circuit photocurrent density ( J sc), and total solar-to-electric conversion efficiency ( η ) for DSCs. Optical results revealed that SD-11 and SD-11 mono have higher molar extinction coefficients, narrower HOMO−LUMO gaps compared to N719. Hence, it was found that SD-11 exhibited remarkably greater J sc than SD-11 mono and interestingly showed comparable extinction coefficients. However, in optimized conditions, SD-11 showed a higher J sc of 22.1 mA cm −2, V oc of 0.68 V with (% η) of 8.7 compared to J sc of 14.4 mA cm −2, V oc of 0.63 V and with (% η) of 5.8 for SD-11 mono whereas N719 attained a J sc of 15.9 mA cm −2, V oc of 0.74 V with (% η) of 7.6 under the same experimental device conditions. It was concluded that SD-11 outperformed SD-11 mono in photovoltaic performance when anchored on TiO2, owing to better light-harvesting ability. These results clearly demonstrated that the enhancement of the photovoltaic performance in SD-11 can be attributed to the presence of more number of –Br group. Highlights: Two novel heteroleptic bipyridyl Ru(II) complexes (SD-11 & SD-11 mono) were established. Highlights the striking effect of –Br on the photocurrent and photovoltage in DSSC. SD-11 outperformed SD-11 mono in photovoltaic performance due to better light-harvesting ability. Enhancement of the photovoltaic performance in SD-11 can be attributed to the presence of more number of –Br group. Molecular modulations of electron donating brominated-TPA based Ru(II) dyes.